KEPUASAN KERJA MEMEDIASI KESELAMATAN DAN KESEHATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - KRISTIN JUWITA (STIE Indonesia Malang, 2017)
This study to determine the effect of occupational health and safety and work environment on performance of employees through job satisfaction. This study uses a quantitative approach with the method of collecting data through questionnaires, observation, documentation, and interviews. Total population in this study are 250 production employees with 69 respondents as sample and using random sampling techniques. Data analysis technique using path analysis, the results indicating the important role of safety and health and work environment on employee job satisfaction, there are influence of occupational safety and health and work environment on employee performance. However, the results showed that there is a weak influence between safety and health and work environment on performance of employees through job satisfaction. Keywords: occupational health and safety, work environment, job satisfaction, employee performance